Swara Yoga and psycho-physiological recovery: A review of nasal cycle science - Purnima Chetry; Lata Apara Deori; Payel Das; S. Lakshmi Kandhan (Yoga-Mimamsa)
Swara Yoga, an ancient yogic practice focuses on the control of breathe through specific nostrils, has significant effects on psychological, physiological, and psychophysiological functions. This review aims to synthesize existing evidence on Swara Yoga’s influence on brain hemispheric activity and psychophysiological functions regarding physical and mental recovery. Right-nostril breathing (Pingala) is linked to the sympathetic nervous system and left-brain activity, enhancing cognitive functions such as verbal ability and stimulating metabolic activity. In contrast, left-nostril breathing (Ida) activates the parasympathetic nervous system, promoting relaxation, reducing stress, and improving cardiovascular and sleep health. Alternate-nostril breathing balances both sympathetic and parasympathetic activity, improving autonomic regulation, reducing anxiety, enhancing memory recall, and increasing parasympathetic tone. There is currently no direct empirical evidence examining the specific effects of Swara Yoga on psychological and physiological recovery, indicating a notable gap in the scientific literature that warrants focused investigation. This study establishes the relationship between psychological and physiological recovery by drawing on existing research highlighting the impact of Swara Yoga on enhancing both psychological and physiological functions. It presents an integrated perspective on how nostril breathing manipulation techniques can influence overall recovery, suggesting the therapeutic applications in managing stress. This approach is advantageous not only for athletes seeking enhanced performance and quicker recovery in the sense of regulation of blood lactate, HRV, cortisol hormones, and other related parameters but also for the general population aiming to reduce stress and improve overall well-being.